2017
DOI: 10.1002/app.46000
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan functionalization with a series of sulfur‐containing α‐amino acids for the development of drug‐binding abilities

Abstract: Chitosan (Chi; 0.5 g) in 69.66 mM aqueous acetic acid was mixed with 312.4 mM methionine (methi) at 0.01 mL/s to disperse and cause optimum collisions for supporting condensation reactions through ANH 2 of Chi and ACOOH groups of methi. The functionalized chitosan (f-Chi) product with methi developed an amide bond, which was represented as methi-functionalized chitosan [Chi-NHAC(@O)-methi]. Both the 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and Dean-Stark methods were followed for Chi functionalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…SPHR was synthesized by solution polymerization using acrylic acid as the monomer, ammonium persulfate and sodium bisulfite as initiator and N-maleyl chitosan as crosslinking agent. [32,33] The reactions were operated under the conditions: monomer concentration 20 wt %, neutralization degree of acrylic acid 50%, initiator concentration 0.2%, cross-linker concentration 1% and 60 8C. Water absorption of the SPHR is 505.7.…”
Section: Synthesis Of Sphrmentioning
confidence: 99%
See 1 more Smart Citation
“…SPHR was synthesized by solution polymerization using acrylic acid as the monomer, ammonium persulfate and sodium bisulfite as initiator and N-maleyl chitosan as crosslinking agent. [32,33] The reactions were operated under the conditions: monomer concentration 20 wt %, neutralization degree of acrylic acid 50%, initiator concentration 0.2%, cross-linker concentration 1% and 60 8C. Water absorption of the SPHR is 505.7.…”
Section: Synthesis Of Sphrmentioning
confidence: 99%
“…PPC not only exhibits interesting material properties, but also has the additional environmental advantages resulting from their biodegradability. [29,30] Huang et al [31] and Li et al [32] reported PPC and its derivatives were used as controlled drug materials for PPC microcapsules. Microspheres were found to have a certain effect on the controlled release of drug.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, LGT depicted as the 4𝑓 #𝑒 ~𝐹𝐸 could replace the expensive prisms used for splitting a light for faster photocatalysis of industrial effluents 14 . 𝐿𝑆𝑁𝑅 could also be doped with proteins, chitosan, carbohydrates/cellulose as biotemplet with 4𝑓 #𝑒 ~𝐹𝐸 interface for biophysical applications 15 . 𝐿𝐺𝑇 with 4𝑓 #𝑒 ~𝐹𝐸 an energy simulator could trap a solar radiation for bio and piezoelectric sensors and minimizes a light scattering, and quantum confinements within optoelectronics 3,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike MOF of transition metals, the lanthanide organic framework (LOF) could create a huge vacancy of applications with higher frequency of recycling and energy storage 17 . The functional edges (FE) and 𝜋 conjugations of 𝐺𝑂 with photon (ℎ𝜈) generates wavefunction (𝜓) in different phases (𝜑) but the 4𝑓 #𝑒 ~𝐹𝐸 interface photocatalyzed a dye in a shorter time with intensified redox cycle (𝑅𝑂𝐶) [14][15][16] . The LSNR and LGT could affect salt bridges, electrostatic, and peptide bonds of protein by generating thermodynamic parameters tuned by 4𝑓 #𝑒 electrons 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the most naturally occurring polysaccharides, which are either anionic or neutral, such as cellulose, starch, or alginate, CS is a polycation. The free amine groups, which are responsible for the polycationic character, bear nonbinding electrons providing donor properties suitable for coupling to electrophiles, for example, for the formation of imines or amides [4,5].…”
Section: Introductionmentioning
confidence: 99%